2022
DOI: 10.1136/ard-2022-222787
|View full text |Cite
|
Sign up to set email alerts
|

Tenderness and radiographic progression in rheumatoid arthritis and psoriatic arthritis

Abstract: ObjectiveThe aim of this study was to assess the predictive value of tenderness in the absence of swelling with consideration of other potential risk factors for subsequent radiographic progression in rheumatoid arthritis (RA) and psoriatic arthritis (PsA).MethodsClinical and sonographic (grey scale and power Doppler (PD)) examination of 22 joints of the hand were performed in patients with RA and PsA. The impact of tenderness on progression after 2 years was analysed in non-swollen joints for RA and PsA separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Of note, having tender but not swollen joints may reflect noninflammatory pain in some, but for others it may be a milder manifestation of their inflammatory arthritis. One study of 55 patients with RA and 18 patients with psoriatic arthritis found that tender but not swollen joints were associated with subsequent radiographic progression 31 . We performed a sensitivity analysis adjusting for CRP that did not change our results.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Of note, having tender but not swollen joints may reflect noninflammatory pain in some, but for others it may be a milder manifestation of their inflammatory arthritis. One study of 55 patients with RA and 18 patients with psoriatic arthritis found that tender but not swollen joints were associated with subsequent radiographic progression 31 . We performed a sensitivity analysis adjusting for CRP that did not change our results.…”
Section: Discussionmentioning
confidence: 92%
“…One study of 55 patients with RA and 18 patients with psoriatic arthritis found that tender but not swollen joints were associated with subsequent radiographic progression. 31 We performed a sensitivity analysis adjusting for CRP that did not change our results. Further study is needed to determine how to better identify noninflammatory pain in our patients with RA, because management would differ from that of RA.…”
Section: Discussionmentioning
confidence: 99%
“… 15 In another study investigating the impact of tenderness on PsA, baseline radiographic damage was the only variable significantly associated with radiographic progression, despite many factors not having a marked influence, including joint tenderness. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The severity of PsA is independent from the severity of psoriasis PsA, which has in most cases mild to moderate disease with a fluctuating course. However, bone erosions can occur early in the disease’s course and lead to disability and impaired function of affected joints and bones [ 18 ]. The Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) has recognized different domains of PsA including synovitis, enthesitis/dactylitis, nail, skin, and axial involvement [ 19 ].…”
Section: Metabolic Comorbidities Of Psoriasismentioning
confidence: 99%